UPAYA PENINGKATAN KEBERSIHAN LINGKUNGAN GUNA MENGURANGI SAMPAH DI KAWASAN DESA JENGGLUNGHARJO KABUPATEN TULUNGAGUNG - Inatsan Latifah, Dahlia; Roihan Arya Ramadhani; Wildan Rizqi Fajari; Slamet Fauzan (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Jengglungharjo Village is a village located in a lowland area within the Tanggunggunung subdistrict, Tulungagung Regency. Jengglungharjo Village consists of five hamlets with a total population of 5,395 residents. The residents of Jengglungharjo Village mainly work as farmers, livestock breeders, and fishermen. Through direct observation in the five hamlets of Jengglungharjo Village, it was often found that there are inadequate waste disposal facilities as garbage collection points. Addressing this issue requires increased attention to the availability of trash bins in Jengglungharjo Village to enhance the cleanliness of the village area. The construction of trash bins is a step taken to improve cleanliness levels, increase the availability of trash bins, and minimize the accumulation of waste in Jengglungharjo Village. Efforts to improve cleanliness are also carried out through village clean-up activities. The method used involves physical intervention by creating trash bins as an effort to increase the number of waste disposal facilities around Jengglungharjo Village. This initiative will result in the production of trash bins that will be distributed to several points in Jengglungharjo Village where additional bins are needed.